NextGen agroadvisory boosts Ethiopian wheat yields by 38% - Tamene, Lulseged D.; Mesfin, Tewodros; Liben, Feyera; Worku, Wuletawu; Ebrahim, Mohammed; Tilaye, Asmalu; Tesfu, Daniel; Getachew, Gashaw; Hawinet, Bekele; Kebede, Ayele (2024)
Site-specific, season-smart fertilizer recommendations boosted wheat yields by 38% among smallholder farmers in Ethiopia, prompting government attention for wider promotion. Piloted with key partners, the approach reached over 50,000 farmers, with 8,316 (16.6%) adopting the recommendations, 20% of whom were women. The initiative marked a shift from the traditional blanket recommendations to precise, digitally-enabled fertilizer advice, efficiently distributed through agile channels to local extension agents and farmers, highlighting effective tailored agronomic advice in Ethiopian wheat-growing areas.